2018
DOI: 10.1177/2333721418778187
|View full text |Cite
|
Sign up to set email alerts
|

Support From Migrant Children and Depressive Symptoms Among Chinese Older Adults in Transnational Families

Abstract: International migration creates important consequences both for migrants and the family members they leave behind. Prior research has noted not only the adverse effects of children’s migration on parents’ mental health but also the fact that family ties and closeness can persist because of supportive exchange despite geographical distances. This study examined the associations between economic and emotional support from migrant children living abroad and depressive symptoms among Chinese elders in transnationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Consistent with the second hypothesis, urban but not rural participants receiving emotional support from adult children had fewer depressive symptoms, and a higher percent of urban participants reported receiving sufficient intergenerational emotional support than rural participants. This significance of emotional support from adult children corresponds with previous studies on older Chinese citizens ( 4 , 39 ) and older adults (including Chinese immigrants) in developed countries ( 28 , 29 , 35 ). With economic function detached from modern families, intergenerational relationships are less structurally defined and more personal ( 18 ), and emotional ties are based more on “verbal communication, understanding, sharing thoughts, and showing feelings” ( 40 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with the second hypothesis, urban but not rural participants receiving emotional support from adult children had fewer depressive symptoms, and a higher percent of urban participants reported receiving sufficient intergenerational emotional support than rural participants. This significance of emotional support from adult children corresponds with previous studies on older Chinese citizens ( 4 , 39 ) and older adults (including Chinese immigrants) in developed countries ( 28 , 29 , 35 ). With economic function detached from modern families, intergenerational relationships are less structurally defined and more personal ( 18 ), and emotional ties are based more on “verbal communication, understanding, sharing thoughts, and showing feelings” ( 40 ).…”
Section: Discussionsupporting
confidence: 89%
“…For example, with older participants from Myanmar, Vietnam, and Thailand, researchers found that financial but not emotional support from adult children predicted fewer depressive symptoms (27). In contrast, with participants from urban China, emotional but not financial support from adult children predicted fewer depressive symptoms in old age (4). Other studies in Japan and Spain found that both emotional and instrumental support from adult children was linked to fewer depressive symptoms (28, 29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding psychological well-being, the included six articles detail the potential risk factors and impacts of psychological distress among global Chinese populations and challenge our assumptions about how individual and familial factors relate to psychological distress and well-being in immigrant populations. Specifically, different forms of psychological distress may have negative impacts of cognitive function ( Y. Chen, Wang, Liang, Sun, & Dong, 2018 ; Kong, Davitt, & Dong, 2018 ), but psychological distress may be buffered by individual, social, and familial resources for both Chinese in China and in the United States ( Chao, Zhang, & Dong, 2018 ; M. Li & Dong, 2018 ; Liu et al, 2018 ; Wang & Dong, 2018 ). In addition, articles in this issue examine how neighborhood and community may impact minority immigrant older adult populations.…”
Section: Study Findingsmentioning
confidence: 99%
“…Chen, Wang, Liang, Sun, & Dong, 2018; Kong, Davitt, & Dong, 2018), but psychological distress may be buffered by individual, social, and familial resources for both Chinese in China and in the United States (Chao, Zhang, & Dong, 2018; M. Li & Dong, 2018; Liu et al, 2018; Wang & Dong, 2018). In addition, articles in this issue examine how neighborhood and community may impact minority immigrant older adult populations.…”
Section: Study Findingsmentioning
confidence: 99%